Utilization of Autoplay to Develop Excretion System as Learning Media with Engklek Game Evaluation - Anantyarta, Primadya; Wicaksono, Azizul Ghofar Candra (Journal of Natural Science and Integration, 2022)
The use of interactive multimedia as learning media is necessary to assist the learning process. The use of Autoplay in developing learning media enables the teachers to produce very good media in facilitating students' needs in learning excretory system material. The addition of an Engklek  game is also very helpful in developing cognitive levels and activating students' motor skills. The method used in the use of Autoplay to develop learning media refers to the model developed by Lee and Owens 2004, namely the Analysis, Design, Development, Implementation and Evaluation (ADDIE) model. This development research stage is only carried out until the Analysis, Design, Development stage, because this research is only limited to developing learning media. After arriving at the development stage, the product is packaged in the form of a Compact Disk (CD) and submitted to the excretory system learning material expert and learning media expert to assess the feasibility of the product being developed, then tested on a small scale by expert practitioners and students to assess the quality of the product learning. The results of the validation of the material experts demonstrated the percentage of eligibility 95.71% with very good criteria and the results of the validation of the media experts disclosed the percentage of eligibility 97.14% with very good criteria. Supported by the results of the readability test of 10 student respondents and 1 practitioner who gave criticism and suggestions that the use of Autoplay to develop excretory system learning media with the evaluation of the designed Engklek  game was very good and feasible to use.Keywords: autoplay, media development, excretory system, engklek traditional game.